The Prague Stroop Test: Normative standards in older Czech adults and discriminative validity for mild cognitive impairment in Parkinson's disease - Bezdicek, Ondrej; Lukavsky, Jiri; Stepankova, Hana; Nikolai, Tomas; Axelrod, Bradley N; Michalec, Jiri; Růžička, Evžen; Kopecek, Miloslav (Journal of clinical and experimental neuropsychology, 2015)
OBJECTIVE: The aim of this study was to provide normative data for older and very old Czech adults on the Prague Stroop Test (PST) and to test its discriminative validity in individuals with Parkinson's disease mild cognitive impairment (PD-MCI). METHOD: The construction of the PST was modeled after the Victoria Stroop Test. We examined 539 participants aged 60-96 that met strict inclusion criteria. After, we compared the PST scores for a group of 45 PD-MCI patients with a healthy adult sample (HAS) of 45 age- and education-matched individuals. RESULTS: I. In the non-clinical sample, robust age- and education-related influences were observed on all PST scores. No gender effect was noted. II. For clinical cases, interference condition (PST-C) was able to discriminate between PD-MCI and HAS (all scores ps < .01). Area under the curve (AUC) was 77% when a screening cut-off of ≤ 27 s was used, showing sensitivity of 82% and specificity of 53%. A more conservative diagnostic cut-off of ≤ 33 s showed sensitivity of 60% and specificity of 80%. DISCUSSION: The present study provides PST normative data for basic, interference, and error scores stratified by age (60-96 years). PST appears to be a helpful tool for the diagnostics of PD-MCI especially in research settings at Level II (Litvan et al., 2012) and for PD-MCI attention/working memory and executive function subtyping.
Keywords: Analysis of Variance; Male; Aging; longitudinální studie; ROC Curve; Česká republika; kognitivní dysfunkce; Parkinson’s disease; Normative data; Stroop Test; Aged; mužské pohlaví; senioři; Cognitive Dysfunction; referenční hodnoty; diskriminační analýza; Inhibition; Czech Republic; Reference Values; senioři nad 80 let; lidé; ženské pohlaví; analýza rozptylu; Discriminant Analysis; Humans; Functional Laterality; Mild cognitive impairment; Aged, 80 and over; Age Distribution; Longitudinal Studies; věkové rozložení; Female; Parkinson Disease; Parkinsonova nemoc; ROC křivka; lidé středního věku; funkční lateralita; Middle Aged; Stroopův test